Identification of Microrna in Pediatric Latent Tuberculosis: A Preliminary Study in Indonesia - Ayling Sanjaya (Journal of Global Pharma Technology, 2020)
Background: Pediatric tuberculosis (TB) is a major health problem in the world and Indonesia. Latent tuberculosis infection (LTBI) in children can be developed in to active state. It is difficult to prevent LTBI due to the lack of specific and diagnostic biomarkers. Research of microRNA (miRNA) conducted to identify profile of miRNA expression among pediatric LTBI specifically in Indonesia. This suggests that miRNA can be one of the tools to diagnose LTBI in children that needs to be developed. Aims: To identify specific miRNA expression in Indonesian pediatric latent tuberculosis infection. Methods: This research was an observational analytic study using a cross-sectional study design. The study used whole blood of healthy control children who had never received BCG immunization and children diagnosed LTBI. Profiling and identified miRNA expression with microarray analysis. Results: Four LTBI and two healthy control children were included in this study. Extraction of RNA with whole blood were done and profiled with gene chip microarray. Fold change >2 or